KAJIAN ANISOTROPY OF MAGNETIC SUSCEPTIBILITY (AMS) BATUAN GRANITIK SITE LOLI DONGGALA, PROVINSI SULAWESI TENGAH - Muslimin 1; Muhammad Rusli M (Fakultas Teknik UMMU, 2020)
The measurement of Anisotropy Magnetic Susceptibility (AMS) has been carried out to determine the magnetic fabric on granitic rocks in the village of Loli, regency of Donggala, Central Sulawesi province. Specimen measured rock taken from seven stations were prepared a cylindrical shape with a diameter of 2.54 cm and a length of 2.3 cm Magnetic Hand Specimen Drill (MHSB). Measurement of susceptibility conducted using MS2 Bartington susceptibility meter is equipped with sensors MS2B. Sensor MS2B working in two frequencies (465 Hz and 4650 Hz). AMS studies performed using variations in measurements of eight directions (AMS-8). The results of measurement, the average value susceptibility of rock is 1,298x10-5 (SI), Value Degree of anisotropy (P) average of 5.8%. Based on the Flinn-type diagram shows that the magnetic minerals tend to be oblate.